Fabrication of graphene-magnetite multi-granule nanocluster composites for microwave absorption application. (December 2019) - An, Boo H; Park, Bum C; Yassi, Hamad A; Lee, Ji S; Park, Jung-Rae; Kim, Young K; Ryu, Jong E; Choi, Daniel S
Ferrite multi-granule nanoclusters are fabricated for microwave absorption materials in different sized particles and granules by modified polyol process. Various sizes of ferrite nanoclusters are placed on graphene-based composites and the behavior of their microwave absorbing properties is studied. The absorbing properties are measured using the free-space method with two horn antennas for X-band range (8.2 GHz–12.4 GHz). Relative permittivity and permeability values are calculated in measured frequency domain. The absorption coefficient changes by forming ferrite-graphene composites are presented as well.